2017
DOI: 10.1177/0148607116678196
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Year Follow‐up of a Randomized Controlled Nutrition Intervention Trial in Very Low‐Birth‐Weight Infants

Abstract: This randomized controlled hypothesis-generating study demonstrated no beneficial effect of early high-dose AA administration and mixed fat emulsions on survival and neurodevelopmental outcome in VLBW infants, although growth was enhanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…The study of Blanco et al was a secondary analysis of a study originally designed with the aim of reducing hyperkalaemia and it was not powered for neurodevelopment. Recent, larger studies did not observe short [48] or long term beneficial effects of increasing amino acid in the early phase [49,50]. Morgan et al showed an improved head circumference growth by both increasing parenteral amino acid and caloric intake, so no definite conclusion can be drawn on the effect of amino acids alone [21].…”
Section: High Versus Low Amino Acid Intakesmentioning
confidence: 99%
“…The study of Blanco et al was a secondary analysis of a study originally designed with the aim of reducing hyperkalaemia and it was not powered for neurodevelopment. Recent, larger studies did not observe short [48] or long term beneficial effects of increasing amino acid in the early phase [49,50]. Morgan et al showed an improved head circumference growth by both increasing parenteral amino acid and caloric intake, so no definite conclusion can be drawn on the effect of amino acids alone [21].…”
Section: High Versus Low Amino Acid Intakesmentioning
confidence: 99%
“…Among these, 6145 studies were excluded after reviewing titles and abstracts, leaving 53 articles for full text review for eligibility ( Figure 1 ). Finally, nine studies were selected with proper eligibility [ 9 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. One study [ 20 ], which was a planned follow-up of a previous RCT [ 19 ], was based on the same population and was therefore considered an identical study.…”
Section: Resultsmentioning
confidence: 99%
“…In other study by Jorine A. Roelants et al to determine the effect of early aggressive parenteral nutrition (PN) on long-term outcome in very low birth weight newborns, the findings demonstrated that the he primary use of highdose amine-acid administration and mixed fat emulsions, although improving the growth, has no positive effect on neuronal growth in very low birth weight newborns [23]. The study by dit Trolli SE to determine of the effect of cumulative intakes of proteins, carbohydrates, lipids and energy during the first 28 days of life on the weight gain in the first 28 days of life, showed that there is a significant statistical association between the cumulative lipid intake at 14 days of life with the developmental quotient (P-Value: 0.04) [24].…”
Section: Discussionmentioning
confidence: 98%